(untitled) (American Journal of Islam and Society, 2012)
The Sayed Case in the District Court of Western Australia required the court to decide on the issue of a witness in niqab. The defendant, in this case a Muslim man, said that a prosecution witness wearing niqab created a disadvantage for the defense and wanted her to provide her testimony without a face veil. While this is a narrow characterization of the issue for the court, the case sparked much controversy including calls for the government to regulate forms of Muslim women’s dress as was the case in France and Belgium. At present, while many Muslim women in Australia do not cover either their hair or face, the common law and statute do not prescribe or proscribe any form of dress for Australians. The call by some Muslims, such as in the Sayed Case, for the imposition of limits on Muslim dress, employs the scholarship of foreign Muslims who they support. This paper calls for the rejection of such prescriptive formulations of both Australian law and the local expressions of Islamic law. Others such as Katherine Bullock, an Australia Muslim academic, support women’s choice in the broadest terms ‒ and this paper supports the primary sources of Islam, the traditional Islamic scholarship, and is deeply acculurated in the Australian ethic of personality autonomy and choice for all, including Muslims women. While they are both independent works, both Bullock’s work and the common law as articulated by the judge in the Sayed Case are strongly supportive of allowing women the choice of covering themselves. This paper contends that Australian common law, as confirmed in the Sayed Case, is reflective of a broader Muslim consensus and should be retained as the status quo.